Do hedonic rewards at online communities affect consumer-fashion brand engagement? A PLS approach - Bilro, R.G.; Loureiro, S. M. C.; Cabaço, M. G. (2019 Global Fashion Management Conference at Paris, 2019)
Over the past few decades, consumers have become increasingly demanding, especially for the hundreds of brands that come up daily. Brands, on the other hand, must adapt constantly to these changes so that they become visible in a market as competitive as it is today (Zhang, Jiang, Shabbir, & Du, 2015). Moreover, with a technologically more developed environment, consumers start to set aside paper journals, coffee conversations, or even phone calls, and start giving more importance to digital atmosphere in their daily lives. With the arise of online brand communities as privileged platforms of interaction and information sharing between brands and consumers, these last ones cannot only access to up-to-date information about different brands, but also obtain several rewards such as hobbies, prizes, discounts, among others (Batra & Keller, 2016). In addition, they can comment and talk with other consumers and/or fans of a particular brand, and share their experiences (Schamari & Schaefers, 2015). In this sense, the current research aims to explore the importance of the hedonic reward in the consumer engagement with online communities of fashion brands. Furthermore, we intend to analyses the role of hedonic versus utilitarian rewards that this type of online platforms can offer to consumers. This research gap arises from the need to further explore consumer’s interaction motivations toward this type of platforms. To do so, we perform a quantitative study with data collected from consumers through an online questionnaire, with a sample of 367 respondents. With this research we intend to emphasize that fashion brands, and companies in general should deepen their presence in online communities, using hedonic rewards to promote consumer engagement, and consequently providing a continuous improvement of the brand itself. Thus, the main aim is to explore the relationship between different dimensions of Baldus et al. (2015) of online brand community engagement on subjective well-being and brand advocacy.